(untitled) (London, 1956)
This book assessing the European scene, industry's needs, the social factors, the public sector's response.
Keywords: Công nghiệp công nghệ sinh học,Biotechnology industries; Chính sách chính phủ,Hội nghị,Government policy,Government policy,Congresses; Châu Âu,Europe